2021
DOI: 10.1136/jech-2021-216637
|View full text |Cite
|
Sign up to set email alerts
|

Partner loss and its effect on frailty trajectories: results from the 13-year follow-up Survey of Health, Ageing and Retirement in Europe (SHARE)

Abstract: BackgroundFrailty is a geriatric syndrome closely linked to a variety of adverse health outcomes. Thus, it is important to identify factors associated with the development of frailty. It was the aim of this study to examine, if, and to what extent partner loss, a highly stressful life event, affects frailty trajectories of community dwelling adults aged 50 or older.MethodsUsing six waves of panel data from the Survey of Health, Ageing and Retirement in Europe (SHARE), we investigated the effect of partner loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…This indicates that dental care may help alleviate the impact of tooth loss on functional capacity decline, which is also supported by the results of the present study, in line with the results that the low-impact subgroup on intellectual activity was more likely to use dental prosthesis (Appendix Table 4). Having a partner provides social support, and losing a partner can accelerate frailty among older people (Oberndorfer et al 2022). The present study identified these potential effect modifiers that can independently or cumulatively increase the effect of tooth loss.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that dental care may help alleviate the impact of tooth loss on functional capacity decline, which is also supported by the results of the present study, in line with the results that the low-impact subgroup on intellectual activity was more likely to use dental prosthesis (Appendix Table 4). Having a partner provides social support, and losing a partner can accelerate frailty among older people (Oberndorfer et al 2022). The present study identified these potential effect modifiers that can independently or cumulatively increase the effect of tooth loss.…”
Section: Discussionmentioning
confidence: 99%
“…A study in SHARE showed that loneliness and social isolation were associated with the risk of developing frailty or pre-frailty status, with relative risk ratio of 1.14 and 1.68, respectively, with the presence of loneliness; and 1.17 and 1.84, respectively, with social isolation 22 . Another study analysed the six waves of the SHARE study and extracted data from 79874 participants in partnerships and 3620 participants who lost their partners, finding that while men and women experienced an initial drop in frailty after the loss, women were more likely to recover the lost frailty points overtime while the effects on frailty persisted in men 23 . Also using SHARE, Ilinca and Calciolari showed that frailty was associated with greater utilisation of primary healthcare and hospital services 24 .…”
Section: Associated Factorsmentioning
confidence: 99%